2023
DOI: 10.1002/hlca.202200202
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Crystals, Jack, Conductivity and Magnetism

Abstract: In Memory of Jack DunitzRecently, the application of magnetic fields to chiral chemical systems has been rewarding. In a forwardlooking 1986 paper, 'Chiral Metals?', Wallis, Karrer, and Jack D. Dunitz forecast 'that the limitation to proper symmetry elements in a chiral conductor could be associated with the emergence of new properties, those connected with interactions between applied electric and magnetic fields and their internal counterparts.' This was a prescient remark, but it has become manifest in ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Because chiral molecules lack a center of inversion, hybrid semiconductors containing chiral organic cations can exhibit properties that are only found in noncentrosymmetric crystal structures, such as second-harmonic generation, , ferroelectricity, , circularly polarized photoluminescence (CP-PL), and CP light detection. Chiral molecules can also afford control of spin-based properties; the chiral hybrid Ruddlesden–Popper perovskites ( R / S -methylbenzylammonium) 2 PbI 4 and ( R / S -methylbenzylammonium) 2 SnI 4 exhibit spin-dependent charge transport due to the chirality-induced spin-selectivity (CISS) effect, , which has enabled a room-temperature spin-polarized light-emitting diode without the use of magnetic components . Furthermore, chiral crystals are a relatively unexplored chemical system with potential for new functionalities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because chiral molecules lack a center of inversion, hybrid semiconductors containing chiral organic cations can exhibit properties that are only found in noncentrosymmetric crystal structures, such as second-harmonic generation, , ferroelectricity, , circularly polarized photoluminescence (CP-PL), and CP light detection. Chiral molecules can also afford control of spin-based properties; the chiral hybrid Ruddlesden–Popper perovskites ( R / S -methylbenzylammonium) 2 PbI 4 and ( R / S -methylbenzylammonium) 2 SnI 4 exhibit spin-dependent charge transport due to the chirality-induced spin-selectivity (CISS) effect, , which has enabled a room-temperature spin-polarized light-emitting diode without the use of magnetic components . Furthermore, chiral crystals are a relatively unexplored chemical system with potential for new functionalities …”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, chiral crystals are a relatively unexplored chemical system with potential for new functionalities. 34 The exciting properties of chiral hybrid perovskite systems motivate an understanding of the interplay of the chiral organic cations and the optoelectronic properties in chiral hybrids with alternative structural topologies. Bismuth and antimony have been exploited to expand the compositional and structural phase space of these hybrid semiconductors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that a small internal magnetic field is generated when a voltage is applied parallel to the axis of a helicoidal conductive crystal, similar to a solenoid. The conductivity is maximized when an external magnetic field aligns with the internally generated field and minimized when the external field opposes the internal one, following the equation Δ R R = 2 γ D / L B · I where γ D/L represents the magnetochiral anisotropy factor between right and left handed twists, B is the magnetic field, and I is the current. Electric magnetochiral anisotropy has been observed in twisted bismuth wires, crystals of a chiral TTF derivative, and carbon nanotubes, among other structures.…”
Section: Future Directionsmentioning
confidence: 99%
“…The origin and amplification of chirality as seen in L‐amino acids and D‐sugars are of great interest because they have been one of the prerequisites for the chemical origin of life. Among the credible theories, 1–28 chiral crystallization of achiral compounds 29,30 is one of the fundamental phenomena of the generation of chirality. Because stereospecific reactions utilizing the chirally oriented crystals as a substrate have been reported, 31–37 enantioenriched chiral compounds could be obtained based on the crystal chirality of achiral compounds.…”
Section: Introductionmentioning
confidence: 99%